Tourism experiences reduce the risk of cognitive impairment in the Chinese older adult: a prospective cohort study - Li, Qian; Guo, Zheng; Hu, Fangli; Xiao, Mengfei; Zhang, Qiang; Wen, Jun; Ying, Tianyu; Zheng, Danni; Wang, Youxin; Yang, Song; Hou, Haifeng (Frontiers in Public Health, 2023)
Given the etiological complexity of cognitive impairment, no effective cure currently exists for precise treatment of dementia. Although scholars have noted tourism's potential role in managing cognitive impairment and mild dementia, more robust empirical investigation is needed in this area. This study aimed to examine the associations between tourism and cognitive impairment and dementia in the Chinese elderly.From a nationwide community-based cohort, 6,717 individuals aged ≥ 60 were recruited from 2011 to 2014, of whom 669 (9.96%) had had at least one tourism experience in the 2 years prior to enrollment. All the participants were then prospectively followed up until 2018. The association between tourism and cognitive impairment was examined by the Cox proportional hazards regression model. The adjusted hazard ratio (aHR) and its 95% confidence interval (CI) were calculated to evaluate the effect of tourism experience on cognitive impairment and dementia.A total of 1,416 individuals were newly diagnosed with cognitive impairment and 139 individuals with dementia onset during follow-up. The incidence of cognitive impairment was significantly lower among participants with tourism experiences (316.94 per 10,000 person-years) than those without such experiences (552.38 per 10,000 person-years). Cox regression showed that tourism decreased the risk of cognitive impairment (aHR = 0.69, 95% CI: 0.41 to 0.62) when adjusted for behavioral covariates and characteristics. Compared with participants without tourism experiences, those with 1, 2, and ≥ 3 tourism experiences had a lower risk of cognitive 4 impairment with the aHRs of 0.72 (95% CI: 0.52 to 0.99), 0.65 (0.42 to 1.01), and 0.68 (0.44 to 0.98), respectively. Tourism experiences also reduced participants' risk of dementia (aHR = 0.41, 95% CI: 0.19 to 0.89).Our findings demonstrated associations between tourism and reduced risks of cognitive impairment and dementia in the Chinese elderly. Thus, tourism could serve as a novel approach to dementia prevention.